Adaptation measures for increasing water security in basins under change - Gesualdo, Gabriela Chiquito (2023)
Climate change and extreme events significantly impact water security in basins worldwide. The increasing frequency and intensity of extreme weather events such as floods and droughts threaten the sustainability of water resources, jeopardizing economic development and social welfare. Therefore, it underlines the importance of adaptation strategies to enhance water security and build resilience in the face of climate change. This thesis aims to put forward risk pooling and index-based insurance as viable adaptation measures to enhance water security and bolster the resilience of catchments experiencing environmental changes in Brazil. We begin with a review of water security in Brazil, analyzing the peculiarities of each geographic region and hydrographic area. This analysis highlights the following challenges and opportunities for water management in Brazil: (1) the need to consider climate change scenarios in current and future policies, (2) improve and invest in non-structural adaptation measures, (3) involve society in the development of these mitigation and adaptation measures, and (4) improve cooperation between researchers and decision-makers. Given these challenges, we proposed the first adaptation measure: risk pooling. In order to do so, we present a novel framework to identify the spatial connectivity of hydrological droughts and propose the risk-pooling regions based on catchment connectivity characteristics. We have identified five regions within the country exhibiting similar drought patterns. These regions serve as a basis for devising risk-pooling strategies. In such strategies, regions located outside the identified drought similarity regions can form risk pooling regions to mitigate the impact of widespread droughts. A case study was applied to propose the second adaptation measure, index-based insurance. The study simulates multi-year and multi-risk index-based insurance for a Water Supply System, considering the impacts of climate change on water availability and demand. Based on the findings of the study case, we can provide suggestions for a contract structure that may be valuable to Brazilian water supply companies. We could assume that water utilities and consumers can regulate and reduce the financial effect of drought and flood disasters by adopting index-based insurance. Overall, we can conclude that the implementation of risk pooling mechanisms and index-based insurance as adaptive strategies in Brazil\'s catchments would improve water security and resilience by reducing the impact of extreme events, managing water shortages, guiding adaptation plans, and mitigating economic losses. This thesis provides a valuable contribution to the understanding of water resource planning and management, providing insights for effective water governance, sustainable development, and improved water security in Brazil.